Pomiędzy przyjemnością a przyjemnością: błazny i łotry tworzą swe listy lektur - Masłoń, Sławomir (Er(r)go. Teoria - Literatura - Kultura, 2011)
Sławomir Masłoń – Between Pleasure and Pleasure: Fools and Knaves Make Their Own Reading Lists Drawing from the Lacanian interpretation of the Shakespearean distinction into fools and knaves the article touches upon the cultural mechanisms behind the making of the contemporary literary canon.